Support for vigilantism in cyberspace: exploring procedural justice, distributive justice, and legal legitimacy - Ireland, Leanna (Criminal justice studies, 2023)
Vigilantism, harmful acts conducted in response to social deviance and criminal activities, are increasingly happening in cyberspace. These cyber acts often have detrimental effects, and efforts at prosecution attempts can be unsuccessful, difficult, or nearly impossible. An understanding of support for cyber vigilantism can help deter activity and mitigate some of the associated harms. The paper, using US-based survey data, tests whether public perceptions of distributive and procedural justice, via perceived legitimacy of the criminal justice system, are associated with support for cyber vigilantism. The findings provide support for the process-based model of legitimacy. Procedural justice is mediated by legitimacy in its influence on support. Distributive justice, however, has a strong direct association with cyber vigilantism support. The paper discusses the implications of the findings for the field of cyber vigilantism.